385 A first-in-human study of lemzoparlimab, a differentiated anti-CD47 antibody, in subjects with relapsed/refractory malignancy: initial monotherapy results. (9th November 2020) - Berlin, Jordan; Harb, Wael; Adjei, Alex; Xing, Yan; Swiecicki, Paul; Seetharam, Mahesh; Nandagopal, Lakshminarayanan; Gopal, Ajay; Xu, Cong; Xu, Cong; Meng, Yuan; Lee, Linda; et al.
Abstract : Background: CD47 blockade using SIRPα-Fc or anti-CD47 antibodies results in inhibition of the 'do not eat' signal and activation of phagocytosis and has emerged as a promising cancer treatment strategy. However, targeting CD47 leads to various hematological toxicities, particularly anemia and thrombocytopenia. Lemzoparlimab (also known as TJ011133 or TJC4) is a fully human, anti-CD47 IgG4 antibody that is endowed with a red blood cell (RBC) sparing property and unique binding epitope, potentially differentiating itself from other CD47 axis targeting therapies. Methods: This phase 1 study (NCT03934814 ) is comprised of 2 parts. Part 1 consists of lemzoparlimab monotherapy dose escalation and 2 separate dose escalations of combination therapy with pembrolizumab or rituximab. The study is a standard 3+3 design. Part 2 is a dose expansion study. During monotherapy dose escalation, patients with relapsed/refractory solid tumors were administered an intravenous weekly dose (1 to 30 mg/kg) of lemzoparlimab to determine tolerability, safety, pharmacokinetics (PK), pharmacodynamics (PD) and anti-tumor activity based on Response Evaluation Criteria in Solid Tumors (RECIST v1.1) and iRECIST. Preliminary data from fully enrolled monotherapy cohorts in Part 1 are reported as of 17 July 2020. Results: Twenty patients with relapsed/refractory solid tumors were enrolled to monotherapy dose escalation cohorts (1, 3, 10, 20 and 30 mg/kg). Lemzoparlimab toxicity was manageable up to 30 mg/kg without a dose-limiting toxicity (DLT) observed. The most common treatment-related adverse events (TRAEs) were anemia (30.0%, n=6), fatigue (25.0%, n=5), infusion-related reactions (20.0%, n=4), and diarrhea (15.0%, n=3). All TRAEs were Grade 1 or 2. A transient, non-dose-dependent average reduction of 1.5 mg/dL (range: 0.4–2.6 mg/dL) in hemoglobin during the first cycle was observed across all cohorts consistent with the results of pre-clinical good laboratory practice toxicity studies. Laboratory or clinical evidence of hemolysis was not observed in any cohort. Preliminary results indicate the PK of lemzoparlimab appears to be linear at mid- to high dose levels following a single dose. CD47 receptor occupancy shows complete saturation on peripheral T cells at peak concentrations of 20 mg/kg and above. Conclusions: Lemzoparlimab appears safe up to 30 mg/kg with favorable PK and PD characteristics in patients with relapsed/refractory solid tumors to date. No TRAEs greater than Grade 2 have been observed. Results will be updated at presentation including available tumor response data. Trial Registration: NCT03934814 Ethics Approval: The study was approved by IRB, approval number 20190733.